2020
DOI: 10.1101/2020.05.26.20112565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saliva as a Candidate for COVID-19 Diagnostic Testing: A Meta-Analysis

Abstract: Objectives: Our aim was to conduct a meta-analysis on the reliability and consistency of SARS-CoV-2 viral RNA detection in saliva specimens. Methods: We reported our meta-analysis according to the Cochrane Handbook. We searched the Cochrane Library, Embase, Pubmed, Scopus, Web of Science and clinical trial registries for eligible studies published between 1 January and 25 April 2020. The number of positive tests and total number of conducted tests were collected as raw data. The proportion of positive tests in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
(112 reference statements)
0
13
0
1
Order By: Relevance
“…This data seem in agreement with previous cross-sectional study (sensitivity and specificity of the saliva sample RT-PCR are 84.2 % and 98.9 %, respectively) [ 12 ]. Furthermore, in recent meta-analysis, the sensitivities for SARS-CoV-2 were 91 % (95 % CI, 80–99 %) and 98 % (95 % CI, 89–100 %) for saliva and for NPS samples, respectively [ 25 ]. Interestingly, Kim and al.…”
Section: Discussionmentioning
confidence: 99%
“…This data seem in agreement with previous cross-sectional study (sensitivity and specificity of the saliva sample RT-PCR are 84.2 % and 98.9 %, respectively) [ 12 ]. Furthermore, in recent meta-analysis, the sensitivities for SARS-CoV-2 were 91 % (95 % CI, 80–99 %) and 98 % (95 % CI, 89–100 %) for saliva and for NPS samples, respectively [ 25 ]. Interestingly, Kim and al.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have showed that OF could be an appropriate sample for diagnosis of SARS-CoV-2 [ 6 , 22 ]. The meta-analysis by Czumbel et al on the reliability and consistency of SARS-CoV-2 viral RNA detection in OF specimens found 91% (95%CI = 80%–99%) sensitivity for OF tests and 98% (95%CI 89%–100%) sensitivity for NPS in previously confirmed COVID-19 infected patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Several preprint articles have reported that the sensitivity of a single RT-PCR test with saliva for diagnosing COVID-19 was in the range 50%-90%; consequently, further studies are warranted. 24,25 Abnormal laboratory results, such as lymphopenia or elevated D-dimer levels, are insufficient to exclude or confirm COVID-19. 1,26 Although typical chest X-ray findings, including interstitial changes and ground-glass opacities located in the bilateral lower lobes, have been reported in patients with COVID-19, a retrospective study revealed that chest X-rays showed no abnormalities in 58.3% of patients with COVID-19.…”
Section: How To Diagnose Covid-19mentioning
confidence: 99%